Turismo religioso, romarias e festas de Frei Damião no Nordeste brasileiro - Chaves, Nadjairo Francisco (2014)
This dissertation aims to understand the prospects of progress that the process of beatification and canonization of Frei Damião can bring to the growth of religious tourism in Pernambuco, having been the focus for pilgrimages and festivals that exist in his honor. It initially is made on a general approach of pilgrimages and religious tourism with focus on overlapping between them, and also point to its historical roots to enter on the question of religious tourism in Brazil. Then we turn our attention to the figure of Frei Damião of Bozzano where strolled briefly through the history of the formation of the Order of Friars Minor Capuchin in Brazil and we enter the life path of Frei Damião in northeastern Brazil , through its missions, and disease death and the process of beatification and canonization. After this step, we proceed to address their pilgrimages and festivals held in honor of Fr Damian to the Brazilian Northeast, with a view to religious tourism and marketing opportunities, and finally, treat existing challenges for the growth of religious tourism in Pernambuco, having focus is on the information received during the interviews conducted by the Guardian of the Convent of St. Felix of Cantalice and Unit Manager of destinations and tourism products of EMPETUR. For this, the methodology used was the literature and documents, for the composition of our theoretical and field research, conducted through interviews, on which one can conclude that the figure of Frei Damião has a great representative for the people northeastern, which considers it a holy symbol of faith and devotion and whose displacements that occur as a result of their festivals and celebrations can be pointed out as an important asset for the growth of religious tourism in the Northeast.